Brefeldin A-ester targets breast cancer cell proliferation, invasion and migration through targeting STAT3 protein expression. (February 2023) - Ding, Haolong; Ouyang, Qianwen; Jiang, Xiaochen; Wu, Xiaobo
Abstract: Brefeldin A-ester (BAE) treatment significantly reduced SkBr3 and MDA-MB-231 cell proliferation in a concentration-dependent manner. It inhibited colony formation in SkBr3 and MDA-MB-231 cells significantly compared to the control cells. In BAE-treated MDA-MB-231 cells, migration and invasion potential showed a remarkable decrease after 72 h of incubation. Treatment with 12 µM of BAE led to a considerable suppression in MMP-2 and MMP-9 protein levels. The apoptotic cell fraction significantly increased in MDA-MB-231 cells at 72 h in comparison to the control cells. Treatment of MDA-MB-231 cells with BAE also caused a prominent suppression in expression of activated STAT3. Molecular docking studies revealed that BAE interacts with glutamic acid and tryptophan amino acids residues of STAT3 protein (4ZIA) through conventional H-bonding with binding affinity of − 9.6 kcal/mol at zero rmsd. Therefore, BAE treatment inhibits growth of breast cancer cells by targeting STAT3 phosphorylation and activation of apoptosis. BAE could have potential as a lead in the development of therapeutic agents for breast cancer. Graphical Abstract: ga1 Highlights: Brefeldin A-ester significantly reduced cell proliferation and migration potential. BAE treatment led to a remarkable suppression in MMP-2 and MMP-9 protein levels. BAE treatment caused suppression in expression of activated STAT3 expression. BAE interacts with glutamic acid and tryptophan amino acids residues of STAT3 protein.